National, state and territory trends in gestational diabetes mellitus in Australia, 2016-2021: Differences by state/territory and country of birth - Wubet Worku Takele; Lachlan L. Dalli; Siew Lim; Jacqueline A. Boyle (Australian and New Zealand Journal of Public Health)
Objective: To examine trends of gestational diabetes mellitus (GDM) in Australia by state/territory and country of birth. Methods: A cross-sectional study was undertaken from 2016 to 2021 using data from the National Diabetes Services Scheme (NDSS) and Australian Bureau of Statistics. The trends were assessed using Average Annual Percentage Changes (AAPCs) and the Cochrane–Armitage test. Results: Nationally, the age-standardised incidence of GDM was 9.3% (95%CI; 9.1–9.4) in 2016 and 15.7% (95%CI; 15.4–15.9) in 2021, representing AAPC of +10.9%. The highest increase was in the Northern Territory, from 6.7% (95%CI; 5.1–8.3) in 2016 to 19.2% (95%CI; 16.9–21.6) in 2021, AAPC=+24.6%. In Southeast Asian-born women, the incidence of GDM rose from 12.2% (95%CI; 11.7–12.7) in 2016 to 22.5% (95%CI; 21.9–23.2) in 2021 (p-trend<0.001). Conclusions: The incidence of GDM has risen in Australia, particularly in the Northern Territory and Victoria, as well as among those born in Southeast Asia and South and Central Asia. Implications for public health: This increase in GDM incidence in Australia underscores the pressing need for location and culturally responsive GDM prevention interventions. The lack of information on some risk factors of GDM (e.g. high body mass index) in the NDSS registry requires further investigation.